IMPLEMENTATION OF PT MEDIA MADANI ULTIMA'S COMPANY PROFILE AS AN INFORMATION MEDIA FOR THE EXTERNAL PUBLIC - Horidatul Bakiyah,; Siti Alpiah,; Achmad Yusuf,; Fajar Diah Astuti, (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
In today's digital era, the rapid advancement of communication and information technology compels business actors to stay ahead in order to remain relevant and competitive. This study employs a descriptive qualitative method, combining interviews, observations, and documentation to gather data. The implementation of a company profile serves as a strategic tool to communicate the existence and operational dynamics of PT. Media Madani Ultima to the external public. Through this initiative, the company aims to enhance public awareness and foster greater trust among the wider community. The author hopes that the company profile will effectively convey essential information about the company’s work systems and services offered to external stakeholders. Upholding professionalism, loyalty, and integrity, PT. Media Madani Ultima is committed to becoming a trusted source of information for the public, contributing to national development and the advancement of the company.